Development of Speech Recognition Technologies By Artificial in-Telligence Systems: A Review of Promising Research and Analysis of Current Achievements - Ramazonov, Nodir; Bozorova, Nasiba; Rakhmonova, Dildora; Babadzhanova, Nazokat (International Journal of Basic and Applied Sciences, 2025)
The relevance of this study lies in the widespread use of speech recognition technologies in everyday life and the vital role of artificial intelligence (AI) in this process. The main purpose of this paper is to review promising research in the development of speech recognition technologies by AI systems, as well as to investigate current achievements in this field. The methodological framework of this study is based on the methods of system analysis, which helped explore the most promising modern research in the development of AI for its subsequent application in speech recognition software. During this study, results were obtained indicating a significant number of promising domestic and foreign research studies on AI. The analysed studies also highlight the broad prospects for the use of AI-based speech recognition technologies for smart homes, voice search, the Internet of Things, and the Industrial Internet of Things, services for people with disabilities. The practical significance of the results obtained, as well as the conclusions of this paper, lies in their further application to create effective AI systems that can be used in various fields of modern science and technology for speech recognition.